Combining Intraoral Scans, Cone Beam Computed Tomography and Face Scans: The Virtual Patient. Issue 8 (November 2018) - Mangano, Carlo; Luongo, Fabrizia; Migliario, Mario; Mortellaro, Carmen; Mangano, Francesco Guido
Abstract : Purpose: The aim of this literature review was to provide an update on the current scientific knowledge in the field of 3D virtual patient science and to identify a possible easy, smart, and affordable method to combine different file formats obtained from different digital devices. Methods: Electronic searches of the Medline database was performed, up to May 2017, for articles dealing with the construction of a 3D virtual patient; the matching of data acquired with different digital devices (cone beam computed tomography, CBCT; face scanner, FS; intraoral scanner, IOS; and desktop scanner, DS) was considered. The inclusion of studies was based on the superimposition of at least 2 different digital sources. Results: Twenty-five studies were selected for subsequent examination. Only 3 studies analyzed the feasibility of superimposition of 3 different types of 3D data (CBCT + FS + IOS/DS). The most frequently used matching procedure was between CBCT and FS and CBCT and IOS/DS. Conclusion: The procedure of superimposition of data from CBCT, IOS, and FS is currently feasible and it is now possible to create a 3D "virtual patient" to better diagnose, plan the treatment, and communicate with patients.